Seismic performance of reinforced concrete columns retrofitted by textile-reinforced mortar jackets. Issue 10 (2nd October 2020) - Dinh, Ngoc Hieu; Park, Sung-ho; Choi, Kyoung-Kyu
Abstract: This study developed a practical retrofit solution for reinforced concrete (RC) columns using textile-reinforced mortar jackets. The main test parameters of this study include the number of textile layers, and the surface treatment methods in lap-spliced regions. The experimental results indicated that the retrofitted solutions by textile-reinforced mortar (TRM) jackets with the proposed details in the lap-spliced regions were quite effective as a means of increasing both the strength and deformation capacity. Moreover, an idealised backbone model to evaluate modelling parameters for the nonlinear analysis of RC columns retrofitted with TRM jackets was constructed, and it showed reasonable agreement with the test results.